2019
DOI: 10.1016/j.suronc.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Association between diabetes and oncological outcomes in patients undergoing neoadjuvant chemo-radiotherapy for rectal cancer

Abstract: Association between diabetes and oncological outcomes in patients undergoing neoadjuvant chemo-radiotherapy for rectal cancer Running head: Diabetes, chemo-radiation and rectal cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The incidence of type 2 diabetes mellitus (T2DM) has been on the rise in recent years. Studies have confirmed that T2DM is significantly positively correlated with the occurrence and development of liver cancer, kidney cancer, colorectal cancer, and pancreatic cancer, among others (5,6). T2DM and TC are both diseases of the endocrine system.…”
Section: Original Articlementioning
confidence: 84%
See 2 more Smart Citations
“…The incidence of type 2 diabetes mellitus (T2DM) has been on the rise in recent years. Studies have confirmed that T2DM is significantly positively correlated with the occurrence and development of liver cancer, kidney cancer, colorectal cancer, and pancreatic cancer, among others (5,6). T2DM and TC are both diseases of the endocrine system.…”
Section: Original Articlementioning
confidence: 84%
“…T2DM is a common endocrine disease, and studies in recent years have suggested that T2DM is significantly correlated with the occurrence of TC (6,17) According to current studies (6,10), abnormal glucose metabolism caused by T2DM may be the main reason for its influence on the occurrence and development of TC. In this study, the differences in age and proportion of stage Ⅰ disease between patients with PTC combined with T2DM and patients with PTC alone were similar to those in previous studies (18).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several epidemiological meta-analyses [ 7 , 8 , 25 , 26 ] and one additional study not included in the previously mentioned meta-analyses [ 27 ] have associated metformin use in patients with T2D and CRC with improved overall and disease-specific mortality. There has been an association in T2D patients who use metformin and who have undergone radical RC resection and subsequent chemoradiotherapy with either improved pathologic complete response and cancer-specific mortality [ 28 , 29 ] or no difference in the outcomes [ 30 , 31 ], when compared to metformin non-user patients with T2D. Our epidemiological study was one of the first to focus solely on RC in the general diabetic population, and we did not find convincing evidence about the association between metformin use, either pre-diagnostic or post-diagnostic, and reduced mortality from RC.…”
Section: Discussionmentioning
confidence: 99%